If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 12) = 30 Reorder the terms: 3(12 + x) = 30 (12 * 3 + x * 3) = 30 (36 + 3x) = 30 Solving 36 + 3x = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 3x = 30 + -36 Combine like terms: 36 + -36 = 0 0 + 3x = 30 + -36 3x = 30 + -36 Combine like terms: 30 + -36 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| 4n+6-2n=2(n+6) | | 7y+3=2x | | -3(x+8)=13x+1 | | 7N-2N+3P+2P= | | -15x=240 | | 2x=7y+3 | | 2-3p=0 | | b/5-3/4=1/2 | | 3(4xy+2x^2+5x^3y)= | | 7(4x+5)= | | 0.5+3.6=4.2-1.5 | | -19x=380 | | x+25x-6y+5y-11= | | 0.96y+2.25-0.06y=7.65 | | 2.2x-13=.6x | | 2x-7y=10 | | 6(x+4)= | | 168=6(-5x-2) | | Y^2-12y=-19 | | 0.5x+0.15(70)=35.5 | | 4y=-80 | | 6=11 | | 9(v+2)-3v=2(3v+4)-9 | | v/7+8=19 | | -2.4x=42.96 | | x^8+4x^7+3x^6= | | -27x^2-15x=0 | | 9x+2(2+x)=5+9x | | 10x-10-x-21=0 | | .75x+10=21 | | -3(2x-4)+5x=2 | | 16.95x+0.5=22.95x+0.02 |